2021
DOI: 10.1108/jet-12-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of ICT connectivity among older adults living in rural subsidized housing: reassessing the digital divide

Abstract: PurposeThis article examines aspects of information communication technology (ICT) connectivity among the understudied population of low-income older adults living in rural and peri-urban subsidized housing. We aim to investigate if variations exist in access and connectivity when economic and housing conditions are constant and use data from northern New England.Design/methodology/approachThe multidisciplinary, mixed-methods approach involved administering structured surveys using iPads with senior residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similarly, just one article collected observation data. Golomski et al (2022) 4). Within the Health articles, these often analyzed older adults' use of digital health information (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, just one article collected observation data. Golomski et al (2022) 4). Within the Health articles, these often analyzed older adults' use of digital health information (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Although the balance between quantitative and qualitative varied across disciplines, Sociology was the only field where qualitative methods dominated. For the mixed methods studies, Golomski et al (2022) The dominant quantitative approach meant that surveys were the most frequent method of data collection (Table 3). 14 of the 33 surveys were distributed face-to-face, 11 were distributed online and four were paper-based only, with the remaining four distributed in some combination of these distribution methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some estimates indicate that only 25% of older residents in low-income housing have reliable internet access [ 18 ]. However, another study on low-income housing residents showed that although the housing communities in the study had access to broadband, few of the residents used the internet [ 19 ]. Thus, providing broadband and a digital device is insufficient.…”
Section: Introductionmentioning
confidence: 99%